The non-specific adenine DNA methyltransferase M.EcoGII. Issue 2 (8th December 2017) - Murray, Iain A; Morgan, Richard D; Luyten, Yvette; Fomenkov, Alexey; Corrêa, Ivan R.; Dai, Nan; Allaw, Mohammed B; Zhang, Xing; Cheng, Xiaodong; Roberts, Richard J
Abstract: We describe the cloning, expression and characterization of the first truly non-specific adenine DNA methyltransferase, M.EcoGII. It is encoded in the genome of the pathogenic strain Escherichia coli O104:H4 C227–11, where it appears to reside on a cryptic prophage, but is not expressed. However, when the gene encoding M.EcoGII is expressed in vivo - using a high copy pRRS plasmid vector and a methylation–deficient E. coli host—extensive in vivo adenine methylation activity is revealed. M.EcoGII methylates adenine residues in any DNA sequence context and this activity extends to dA and rA bases in either strand of a DNA:RNA-hybrid oligonucleotide duplex and to rA bases in RNAs prepared by in vitro transcription. Using oligonucleotide and bacteriophage M13mp18 virion DNA substrates, we find that M.EcoGII also methylates single-stranded DNA in vitro and that this activity is only slightly less robust than that observed using equivalent double-stranded DNAs. In vitro assays, using purified recombinant M.EcoGII enzyme, demonstrate that up to 99% of dA bases in duplex DNA substrates can be methylated thereby rendering them insensitive to cleavage by multiple restriction endonucleases. These properties suggest that the enzyme could also be used for high resolution mapping of protein binding sites in DNA and RNA substrates.